Enhancing content strategy by applying social media as champion advocacy tools - Saary, Sharliza (2021)
Research of enhancing content strategy by applying social media champion advocacy tools is focusing on social media content development for Pusat Internet Komuniti (PIK). All PIK by default should have a Facebook as social media to communicate with local people and all followers through online. From this research, PIK should have the increasing the numbers of Facebook followers, improve the process of developing content and as well as extend the reach of information dissemination. During this research, mix research methodology will apply including past journal review, interview session and survey by using questionnaire. In intervention plan, it proposed to have study on current practice of developing the Facebook content and type of content. After that, intervention will start with develop content using factors (from interview and questionnaire), provide a suitable tools or equipment in developing content process and prepare training for development content process. From the intervention, result can see through the increasing of numbers of followers or numbers of liker of each content. From the result, it will continue for the second intervention (Action Research 2) and the result of the numbers of followers and likers will be measure again and compare with Action Research 1 process.